2013
DOI: 10.1002/wrcr.20436
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution distributed temperature sensing to detect seasonal groundwater discharge into Lake Vaeng, Denmark

Abstract: [1] Distributed temperature sensing (DTS) was used to map spatial and temporal changes in temperature on a 25 m by 6 m lakebed area in the winter (February), spring (May), and summer (August) of 2012. A constant and high discharge of groundwater with the average temperature of around 8 C to the lake will result in either lower (summer) or higher (winter) daily temperatures and reduce temperature variability at the sediment-water interface (SWI). DTS data were used as a proxy for groundwater discharge using thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 35 publications
4
88
1
Order By: Relevance
“…However, isotropic and homogenous conditions rarely exist and spatial distribution of groundwater inflow differs strongly from lake to lake . Experimental studies highlighted a large variety of observed exchange patterns including decreasing seepage with distance from the shoreline (McBride and Pfannkuch, 1975;Brock et al, 1982;Cherkauer and Nader, 1989;Kishel and Gerla, 2002), increasing seepage with distance from the shoreline (Cherkauer and Nader, 1989;Schneider et al, 2005;Vainu et al, 2015), local hotspots of offshore seepage (Fleckenstein et al, 2009;Ono et al, 2012) and a high smallscale variability in near-shore zones (Kishel and Gerla, 2002;Blume et al, 2013;Neumann et al, 2013;Sebok et al, 2013). Most often, complex hydrogeological settings are the reason for deviations from the theoretical pattern of LGD .…”
Section: Spatial Patterns Of Lacustrine Groundwater Discharge and Thementioning
confidence: 99%
See 3 more Smart Citations
“…However, isotropic and homogenous conditions rarely exist and spatial distribution of groundwater inflow differs strongly from lake to lake . Experimental studies highlighted a large variety of observed exchange patterns including decreasing seepage with distance from the shoreline (McBride and Pfannkuch, 1975;Brock et al, 1982;Cherkauer and Nader, 1989;Kishel and Gerla, 2002), increasing seepage with distance from the shoreline (Cherkauer and Nader, 1989;Schneider et al, 2005;Vainu et al, 2015), local hotspots of offshore seepage (Fleckenstein et al, 2009;Ono et al, 2012) and a high smallscale variability in near-shore zones (Kishel and Gerla, 2002;Blume et al, 2013;Neumann et al, 2013;Sebok et al, 2013). Most often, complex hydrogeological settings are the reason for deviations from the theoretical pattern of LGD .…”
Section: Spatial Patterns Of Lacustrine Groundwater Discharge and Thementioning
confidence: 99%
“…Kidmose et al, 2013;Kishel and Gerla, 2002;Schneider et al, 2005;Vainu et al, 2015) and piezometers (Kishel and Gerla, 2002). Two other methods have also been used successfully to investigate exchange patterns between lakes and groundwater: fibre-optic distributed temperature sensing (FO-DTS) (Blume et al, 2013;Sebok et al, 2013) and vertical temperature profiles (VTPs) (Blume et al, 2013;Neumann et al, 2013;Sebok et al, 2013). Both methods use heat as a tracer.…”
Section: Spatial Patterns Of Lacustrine Groundwater Discharge and Thementioning
confidence: 99%
See 2 more Smart Citations
“…Sebok et al [121] used DTS to map spatial and temporal changes in temperature on a lakebed area to confirm the presence of a relatively high discharge of groundwater. The cable was spread out an area of 25 m × 6 m. The measurement through the seasons showed that the extent of the discharge zone was changing as well as its position relative to the shore.…”
Section: Using Dts To Measure Temperaturementioning
confidence: 99%